Model Pembelajaran AKIK BIPA Kepada Pemelajar Philipphine Normal University South Luzon - Misnawati Misnawati (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Indonesian as the national language of the Indonesian nation is also a language studied in various countries. The Indonesian Language Program for Foreign Speakers (BIPA) is a program aimed at teaching Indonesian to foreign speakers. One of the learning models applied in the BIPA program is the AKIK Learning Model (active, communicative, interactive and collaborative). This research aims to: (1) describe the application of the AKIK learning model in BIPA teaching. (2) Analyzing student responses to the AKIK learning model. (3) Identifying the obstacles faced in implementing the AKIK learning model. (4) Evaluate the results of Indonesian language learning using the AKIK learning model. The research results show that the implementation of the AKIK learning model is effective in improving the communication skills and understanding of Indonesian at Normal University South Luzon students. Students responded positively to the AKIK learning model, feeling more motivated and active in learning. However, several obstacles are faced, such as cultural and language differences and limited learning facilities that support technology. This research contributes to the development of the BIPA curriculum by recommending more effective teaching strategies. The results can be used as a reference for teachers and researchers in the field of foreign language teaching, especially Indonesian.